Early-forming massive stars suppress star formation and hierarchical cluster assembly - Lewis, Sean; McMillan, Stephen L. W.; Low, Mordecai-Mark Mac; Cournoyer-Cloutier, Claude; Polak, Brooke; Wilhelm, Martijn J. C.; Tran, Aaron; Sills, Alison; Zwart, Simon Portegies; Klessen, Ralf S.; Wall, Joshua E. (The astrophysical journal, 2023)
Feedback from massive stars plays an important role in the formation of star clusters. Whether a very massive star is born early or late in the cluster formation timeline has profound implications for the star cluster formation and assembly processes. We carry out a controlled experiment to characterize the effects of early-forming massive stars on star cluster formation. We use the star formation software suite Torch, combining self-gravitating magnetohydrodynamics, ray-tracing radiative transfer, N-body dynamics, and stellar feedback, to model four initially identical 104 M ⊙ giant molecular clouds with a Gaussian density profile peaking at 521.5 cm−3. Using the Torch software suite through the AMUSE framework, we modify three of the models, to ensure that the first star that forms is very massive (50, 70, and 100 M ⊙). Early-forming massive stars disrupt the natal gas structure, resulting in fast evacuation of the gas from the star-forming region. The star formation rate is suppressed, reducing the total mass of the stars formed. Our fiducial control model, without an early massive star, has a larger star formation rate and total efficiency by up to a factor of 3, and a higher average star formation efficiency per freefall time by up to a factor of 7. Early-forming massive stars promote the buildup of spatially separate and gravitationally unbound subclusters, while the control model forms a single massive cluster.